Perceived Usefulness as a Mediator in Social Commercial Intention to Use: Perceived Usefulness sebagai Mediator dalam Niat Menggunakan Sosial Komersial - Rahmona, Fitria; Fadliyah, Chairati; Nabillah, Salsa; Haryati, Resti; Evanita , Susi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rise of digital platforms and social media has led to the rapid growth of social commerce (s-commerce), reshaping consumer behavior in emerging markets like Indonesia. Specific Background: While many users engage with platforms like TikTok Shop and Instagram Shopping, sustained intention to use such systems remains varied. Knowledge Gap: Prior research on the Technology Acceptance Model (TAM) often overlooks how Perceived Usefulness (PU) mediates the relationship between Perceived Ease of Use (PEOU) and Intention to Use (IU) in s-commerce contexts, particularly in regions with high digital engagement. Aims: This study investigates whether PU mediates the effect of PEOU on IU among university students with experience using s-commerce platforms. Results: Using SEM-PLS on data from 100 respondents, findings reveal that PEOU has no significant direct effect on IU but significantly affects PU, which in turn significantly influences IU. An indirect path from PEOU to IU via PU is statistically significant. Novelty: The study emphasizes that ease of use alone is insufficient; perceived benefit is critical in motivating continued use in socially driven e-commerce environments. Implications: These findings guide platform developers to prioritize usefulness-oriented features, suggesting that perceived functionality is more influential than interface simplicity in fostering user loyalty.Highlight : Perceived Ease of Use does not directly affect Intention to Use but influences it indirectly. Perceived Usefulness significantly mediates the relationship between ease of use and intention. User intention in social commerce is shaped more by usefulness than technical simplicity. Keywords : Perceived Ease of Use, Perceived Usefulness, Intention to Use, Social Commerce, Mediation Model